KEMUDAHAN PENGGUNAAN, KEPERCAYAAN DAN KEAMANAN TERHADAP MINAT NASABAH DALAM MENGGUNAKAN SELF INTERNET PADA TRANSAKSI PEMBAYARAN PAJAK - Hendi Prihanto; Selfiani Selfiani; Watriningsih Watriningsih (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the magnitude of the effect on the ease of use, trust and security of customer interest in using the Internet for tax payment transactions. The population of this study is all customers who have a savings account at Bank Mandiri Lemigas Jakarta Branch. Sample selection was done by using the Accidental Sampling method. with the method of collecting data using a questionnaire. The data analysis technique in this study used multiple linear regression test in SPSS. The results of this study partially indicate that ease of use and security have a positive and significant effect on customer interest in using Self Internet in tax payment transactions, while the trust variable has no effect on customer interest in using Mandiri Internet in tax payment transactions.